Pengaruh Experiental Marketing Terhadap Loyalitas Pelanggan Kebun Strawberry D’MOOAT - Manengkey, Virgin M.; Tumbel, Tinneke M.; Kalangi, Johnny A. F (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to determine the experiential effect of marketing on customer loyalty at Strawberry D'Mooat Gardens. Experiential Marketing is a marketing approach that involves the emotions and feelings of consumers by creating positive experiences. Customer loyalty is a reliable measure to predict sales growth and customer loyalty can also be defined based on constitutional buying behavior. This study uses a quantitative approach, with a sample of 50 respondents who are customers of Strawberry D’Mooat Gardens who have visited more than twice. The sampling technique in this study is to use Simple Random Sampling. The data analysis method used in this study is a simple linear analysis method which includes validity test, reliability test, hypothesis test and analytical test of the coefficient of determination. It can be seen from the results of testing statistically it can be seen clearly that the independent variable Experiential Marketing affects the dependent variable Customer Loyalty. Based on the results of the study, it shows that experiential marketing has a positive and significant effect on customer loyalty. This shows that experiential marketing is one of the determinants of Customer Loyalty because good experiential marketing will create and maintain customer loyalty.